A Preoperative Scoring System to Predict the Risk of Inadequate Lymph Node Count in Rectal Cancer - Zhang, Hao; Wang, Chunlin; Liu, Yunxiao; Hu, Hanqing; Wang, Guiyu (Frontiers in Oncology, 2022)
Purpose: The aim of this study was to develop and validate a preoperative scoring system to stratify rectal cancer (RC) patients with different risk of inadequate lymph node examination. Methods: A total of 1375 stage I-III RC patients between 2011 and 2020 from the Second Affiliated Hospital of Harbin Medical University were included in the study and randomly divided into development set (n = 688) and validation set (n = 687). Logistic regression model was used to determine independent factors contributing to lymph node count (LNC) < 12. A preoperative scoring system was constructed based on beta () coefficients. The area under the receiver operating curve (AUC) was used to test model discrimination. Results: Preoperative significant indicators associated with LNC < 12 included age, tumor size, tumor location and CEA. The AUCs of the scoring system for development and validation sets were 0.694 (95%CI = 0.648-0.741) and 0.666 (95%CI = 0.615-0.716), respectively. Patients scored 0-2, 3-4 and 5-6 were classified as low-risk group, medium-risk group and high-risk group. Conclusions: The preoperative scoring system could identify RC patients with high risk of inadequate lymphadenectomy accurately and further provide a reference to perform preoperative lymph node staining in targeted patients to reduce the difficulty of 12-node standard.